1994
DOI: 10.1007/bf00203772
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular arbuscular mycorrhizae in floating wetland mat communities dominated by Typha

Abstract: Abstract. Low levels of vesicular arbuscular mycorrhizae were present in floating mats dominated by clones of Typha angustifolia L., T. x glauca Godr., and T. latifolia L. Floating mats composed of rhizomes (underwater-ground stems with high starch accumulation), roots, decaying organic matter, and wind deposited soil, easily supported human activities. The majority of roots isolated from the root cores were connected to Typha rhizomes. Tests employing the gridline intersect method, intensity, spore counts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
0
18
1
Order By: Relevance
“…In our report, we used the occurrence of arbuscules as the only positive indication, by definition, of the establishment of an AM symbiosis, though other authors attributed AM status to species showing only hyphae and/or vesicles in their roots (Stenlund and Charvat 1994;Miller et al 1999). The absence of arbuscules and appressoria, and the occurrence of hyphae and/or vesicles in the roots of nonhost plants, in dead roots, pieces of organic matter, and organs other than roots have been considered by some authors as an indication of the ability of passive colonisation by AM fungi (Park and Linderman 1980;Malajczuk et al 1981;Stasz and Sakai 1984;Giovannetti and Lioi 1990;Giovannetti et al 1994;Giovannetti and Sbrana 1998).…”
Section: Discussionmentioning
confidence: 97%
“…In our report, we used the occurrence of arbuscules as the only positive indication, by definition, of the establishment of an AM symbiosis, though other authors attributed AM status to species showing only hyphae and/or vesicles in their roots (Stenlund and Charvat 1994;Miller et al 1999). The absence of arbuscules and appressoria, and the occurrence of hyphae and/or vesicles in the roots of nonhost plants, in dead roots, pieces of organic matter, and organs other than roots have been considered by some authors as an indication of the ability of passive colonisation by AM fungi (Park and Linderman 1980;Malajczuk et al 1981;Stasz and Sakai 1984;Giovannetti and Lioi 1990;Giovannetti et al 1994;Giovannetti and Sbrana 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Based on RA, the dominant species, namely, A. laevis and R. intraradices, showed different patterns of sporulation and distribution. ese differences in sporulation pattern may be attributed to plant phenological events including new root growth [41], �owering, and fruiting [42]. ey may also suggest differences in AM functionality.…”
Section: Discussionmentioning
confidence: 99%
“…None of the dominant herbaceous plant species along the bog-fen-marsh wetland gradient was VAmycorrhizal (Thormann et al 1999). This was surprising, since previous studies showed that some species of Carex (Wetzel and van der Valk 1996;Cooke and Lefor 1998;Miller et al 1999;Turner et al 2000;Bauer et al 2003), Typha (Stenlund and Charvat 1994;Cooke and Lefor 1998), and various other, less dominant herbaceous plants were VA-mycorrhizal (Currah and van Dyk 1986;Cooke and Lefor 1998). These discrepancies can arise because of different sampling protocols, species examined, and sample sizes.…”
Section: Mycorrhizas and Other Root Endophytesmentioning
confidence: 99%